STUDI DESAIN PONDASI RANCANGAN MASJID AGUNG NURUL KALAM PEMALANG - Prama Arviandi, Reza
Pemalang Regency has an area of 996.1 km2 with a population of Islamic religion totaling 1,490,948 people (BPS, 2018). Pemalang Regency is located on the main arterial route of the north coast of Java Island, Central Java Province. The mosque structure consists of 4 main floors and 1 parking basement. The stages of this final assignment are divided into two, the first part is the design of the foundation in the form of piles and the second part is the design of an open cut retaining wall. The stage for designing the foundation in this final project is to interpret the land data in accordance with the results of testing both from the results of direct testing or from the results of laboratory testing. Furthermore, the interpretation of load data so that the foundation dimensions will be adjusted to the load acting on the foundation. In addition to the foundation must be strong against the load that works, the reduction in the foundation is also taken into account in this final project so as not to cause damage to the beam in the upper structure. Meanwhile, the stages of the final assignment for designing the retaining wall in the form of open cut are the interpretation of soil data, then determining the slope of the land, then the reinforcement design of the retaining wall until its strength and service capability meet the requirements. In addition, the retaining wall in the form of open cut will be analyzed for its stability. In this analysis several methods will be compared against the results given. The planning of the pile and open cut foundation is calculated manually and uses a lot of software assistance such as AllPile, LPile, GROUP, SPColumn, Tekla, and 2D Plaxis. The output obtained from the foundation planning and retaining wall is the dimensions and reinforcement needed to support the working loads.